Analisis Kebijakan Keuangan Jangka Panjang (Studi Kasus Pada Perusahaan PT. Multistrada Arah Sarana, Tbk) - Naland, Harley; Sukartaatmadja, Iswandi (Jurnal Ilmiah Manajemen Kesatuan, 2019)
PT Multistrada Arah Sarana, is one of the companies from Indonesia whose products have met the needs of both domestic and overseas. However, in the past 5 years, the company which is often abbreviated as MASA has experienced a decline in sales which has an impact on Indonesia's economic condition. This study is intended to look at what factors cause a decline of the MASA company by looking at the data within a period of 5 years. Based on the Z-score analysis for the years 2012-2016 obtained a result of 1.80, meaning that it is predicted that MASA has the risk of bankruptcy for some future periods.